Menciptakan Ruang Berekspresi dan Membangun Percaya Diri Anak melalui Pelatihan Menulis Cerita dan Storytelling di Panti Nur Karomah Depok - Zebua, Winda Dwi Astuti; Rosiyanti, Hastri; Utari, Syifa Astasia; Puspaningtyas, Raden Roro Nadya Oktaviany (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Children in foster care often face challenges in expressing themselves and building self-confidence due to limited means of creativity development and social interaction. This community service activity aims to create a space to express and boost the self-confidence of children in Nur Karomah Depok Orphanage through storytelling and storytelling training. The methods used included: (1) analysis of the situation and partners’ needs, (2) implementation of the training with three main stages (coloring pictures, writing short stories, and reading stories in front of the group, as well as (3) participatory evaluation. (23 of 30 participants) who were initially shy managed to read their stories in public The combination of coloring and writing activities proved to be effective as a medium of self-expression, while the small group approach and positive appreciation strengthened children’s self-confidence and encouragement of education also supported this activity. in accordance with the Convention on the Rights of the Child This training succeeds in creating a safe and supportive environment for children to develop literacy skills, communication, and confidence For sustainability, it is recommended that there be regular programs, special accompaniment for us collaboration with shy children..